Co-constructing Frames of Peer Help during Writers Workshop in a Second-grade Bilingual Class. Issue 3 (4th May 2021) - McConnochie, Meredith
ABSTRACT: While research has shown that young children draw upon language ideologies to manage the language choices of peers, little is known about how they use language to negotiate academic identities during peer–peer interactions. Integrating theories of language ideologies, social identities, and frames, this article examines how one teacher and two students in a second-grade bilingual class navigated language ideologies in a transitional bilingual program and negotiated frames of linguistic and academic competency during Writers Workshop. The analysis demonstrates the ways in which the teacher and two students interpreted language ideologies and co-constructed academic frames within which students expressed smart identities by helping peers to complete English writing through bilingual exchanges. These frames indexed district-wide conflicting ideologies of cooperation and individualism and English prioritization that position Spanish as a medium of instruction rather than a linguistic goal.